2013
DOI: 10.1159/000355112
|View full text |Cite
|
Sign up to set email alerts
|

Severe Iron Deficiency Is Associated with a Reduced Conception Rate in Female Rats

Abstract: Background/Aims: Iron deficiency is a global nutritional disorder, especially for pregnant women. There is a close relationship between deficiency in trace elements and unexplained infertility in females. However, the relationship between iron deficiency and unexplained infertility has not been determined. This study was designed to determine the effect of iron deficiency on conception in a rat model. Methods: Female rats were randomly divided into two groups (n = 15 each): an iron-deficiency group fed a low i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
(17 reference statements)
1
23
0
Order By: Relevance
“…Unfortunately, the authors only measured iron intake, and not iron status directly. Later experiments in mice found that inducing dietary iron deficiency, as measured by low hemoglobin and RBC count, led to disruptions in estrous and lower conception rates than mice who were fed a diet with normal levels of dietary iron (Li et al, ).…”
Section: Iron and Fecunditymentioning
confidence: 99%
“…Unfortunately, the authors only measured iron intake, and not iron status directly. Later experiments in mice found that inducing dietary iron deficiency, as measured by low hemoglobin and RBC count, led to disruptions in estrous and lower conception rates than mice who were fed a diet with normal levels of dietary iron (Li et al, ).…”
Section: Iron and Fecunditymentioning
confidence: 99%
“…In peripheral tissues, iron serves as a cofactor for the expression and activation of various metabolic enzymes involved in glycolysis [ 21 ], the TCA cycle [ 22 ], the electron transfer chain [ 23 ], and pentose phosphate pathways [ 21 ]. These pathways are essential for synthesizing ATP and protein.…”
Section: Discussionmentioning
confidence: 99%
“…Before (Diestrus) and 48 h after the PMSG administration, ovaries and serum were obtained from the ND- and LFD-fed mice. Previous studies demonstrated that iron is an essential cofactor for enzymes in many metabolic pathways, including glycolysis, the TCA cycle, the electron transfer chain, and pentose phosphate, produce ATP, DNA, and RNA [ 21 , 22 , 23 ]. The weight of each ovary was measured, and then the ovary was used for the measurements of the E2 (PMSG 48 h) and ATP concentrations (Diestrus).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have confirmed that there is an intimate association between deficiency in trace elements and mysterious infertility in females. A recent epidemiological observational study suggested that women without iron supplementation had a higher risk of ovulatory infertility compared with women who used an iron supplement [13].…”
Section: Pernicious Anemiamentioning
confidence: 99%